PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP PEMAHAMAN KONSEP PESERTA DIDIK DI KELAS VII SMP NEGERI 1 PADANG GANTING KABUPATEN TANAH DATAR - Ilham Wahyudi Amri (Departemen Matematika, 2022)
The first step in learning mathematics is to understand mathematical concepts.Understanding mathematical concepts provides students with a solid foundation for developing other fundamental skills such as reasoning, communication, connections, and problem solving. In fact, students at SMP Negeri 1 Padang Ganting continue to have a poor understanding ofmathematical concepts.This can be seen during observation and in the low scores of students' daily tests, which contain indicators of mathematical concept understanding.The Team Assisted Individualization (TAI) cooperative learning model is used to solve this problem.The goal of this study is to describe the understanding of students' as well as to compare the understanding of mathematical concepts of students who study with the TAI.The research design is quasi-experimental and descriptive, utilizing a Static Group Design.The study's participants were SMP Negeri 1 Padang Ganting class students in the 2021/2022 academic year.Class VII.A served as the experimental class, whereas class VII.B served as the control class.The instrument used in this study is a test of mathematical comprehension.During the study, the outcomes of quizzes were used to describe the growth of mathematical concepts, while the final test was analyzed using the t-test.The final test analysis P-value of 0.046 less than , indicating that students who study using the TAI type cooperative learning model have a greater knowledge of mathematical topics than students who learn using direct learning models. Keywords–team assisted individual, Pembelajaran Langsung, Pemahaman Konsep Matematis